Grain Size Analysis of Beach Sand in the Southern Lombok Coastal Zone - Fawzan Bhakti Soffa (International Journal of Marine Engineering Innovation and Research, 2023)
Beyond its tourist appeal, beach sand plays a significant role in various dimensions, including ecological and geological aspects. This study aims to understand the distribution of sand grains along the coastal zone of southern Lombok through sand grain analysis to support coastal management. Sand samples (n=60) were collected during June-July 2023 from ten different locations along the southern coast of Lombok, including both the intertidal and supratidal zones. The collected samples were dried and sieved to classify their size as Gravel, Very Coarse Sand, Coarse Sand, Medium Sand, Fine Sand, or Silt. Permutational Multivariate Analysis of Variance on transformed log-ratio data confirms that the sand composition in the intertidal zone is significantly different from the supratidal zone in all locations except Bumbang Beach, concluding the dominance of coarser materials in the intertidal zone and finer materials in the supratidal zone. The dominance of coarser materials is found in the southward-facing beaches, which are directly exposed to strong waves, while finer-grained sand is mostly found in covered coastal areas. Most of the coarser materials along Lombok’s southern coastline are composed of well-rounded carbonate sand formed from a large foraminifers, mixed with coral and shell fragments. Extreme dominance of the finer grain class can be found on Selong Belanak and Ekas beaches, indicating a susceptibility to abrasion.